Quo Vadis Perlindungan Kekerasan Seksual: Urgensi RUU PKS Sebagai Perlindungan Korban Kekerasan Seksual - Huda, Muhammad Wahyu Saiful; Izza, Rizqiya Lailatul (Universitas Negeri Semarang in collaboration with Ikatan Penulis Mahasiswa Hukum Indonesia, 2022)
It has been two years since the corona virus pandemic has swept the world. A pandemic that affects every aspect of life, as a result the government is required to provide security to its people. Various programs are implemented to reduce the spread of Covid-19. But the problems this pandemic has created have also led to crime. More specifically, sexual violence. The increase in cases of sexual violence every year is increasingly worrying. The government, at the Preamble to the 1945 Constitution, must protect its people, including sexual violence. Sexual violence is a physical act that injures the honor of the perpetrator and is related to sex. Sexual violence takes many forms, but Indonesian law only covers rape and obscenity. Indonesian law now cannot protect the people as a whole, it is necessary to reform the law on sexual violence. To answer the problem of sexual violence in Indonesia, Komnas Perempuan submitted a draft law on the elimination of sexual violence. The purpose of the Draft Law on the Elimination of Sexual Violence is to provide protection, treatment and restore the condition of victims. The hope of the Draft Law on the Elimination of Sexual Violence is the realization of environmental conditions without any acts of sexual violence. The journey so that the Draft Law on the Elimination of Sexual Violence becomes ratified requires assistance, because of the many misinterpretations of the existing articles. As well as protecting the transfer of the original purpose of the Draft Law on the Elimination of Sexual Violence.